2014
DOI: 10.1111/apa.12848
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging can be used to explore tactile and nociceptive processing in the infant brain

Abstract: AimDespite the importance of neonatal skin stimulation, little is known about activation of the newborn human infant brain by sensory stimulation of the skin. We carried out functional magnetic resonance imaging (fMRI) to assess the feasibility of measuring brain activation to a range of mechanical stimuli applied to the skin of neonatal infants.MethodsWe studied 19 term infants with a mean age of 13 days. Brain activation was measured in response to brushing, von Frey hair (vFh) punctate stimulation and, in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 31 publications
5
59
0
Order By: Relevance
“…In a study of 19 term infants with a mean age of 13 days, distinct patterns of functional brain activation were evoked by brush and von Frey hair punctate stimulation, which were reduced, but still present, under chloral hydrate sedation. Brain activation increased with increasing von Frey hair stimulus intensity (Williams et al 2015), revealing the ability of the newborn brain to code stimulus intensity. A feasibility study in a single full-term infant (Williams et al 2015) laid the foundation for an fMRI study of 10 newborn infants, which identified the network of brain regions that are active following pinprick stimulation .…”
Section: Infant Pain and The Cerebral Cortexmentioning
confidence: 95%
See 3 more Smart Citations
“…In a study of 19 term infants with a mean age of 13 days, distinct patterns of functional brain activation were evoked by brush and von Frey hair punctate stimulation, which were reduced, but still present, under chloral hydrate sedation. Brain activation increased with increasing von Frey hair stimulus intensity (Williams et al 2015), revealing the ability of the newborn brain to code stimulus intensity. A feasibility study in a single full-term infant (Williams et al 2015) laid the foundation for an fMRI study of 10 newborn infants, which identified the network of brain regions that are active following pinprick stimulation .…”
Section: Infant Pain and The Cerebral Cortexmentioning
confidence: 95%
“…Brain activation increased with increasing von Frey hair stimulus intensity (Williams et al 2015), revealing the ability of the newborn brain to code stimulus intensity. A feasibility study in a single full-term infant (Williams et al 2015) laid the foundation for an fMRI study of 10 newborn infants, which identified the network of brain regions that are active following pinprick stimulation . The blood-oxygen-level-dependent (BOLD) response in newborn infants was compared with that observed after the same pinprick stimulation in adults, and significant infant brain activity was observed in 18 of the 20 active adult brain regions, including primary somatosensory cortices, anterior cingulate cortex, bilateral thalamus and all divisions of the insular cortices, but not in the infant amygdala or orbitofrontal cortex.…”
Section: Infant Pain and The Cerebral Cortexmentioning
confidence: 95%
See 2 more Smart Citations
“…MEG and functional magnetic resonance imaging (fMRI) studies with adults have identified an extended network of areas activated by somatosensory stimulation that includes the posterior parietal cortex and other areas (Bardouille & Ross, 2008; Porro et al, 2004). Although some work has attempted using fMRI to study tactile stimulation in infants (Archi et al, 2010; Williams et al, 2015), MEG and EEG are likely to remain the main techniques for examining somatosensory processing in infancy due the methodological challenges of fMRI research with this age group.…”
Section: Discussionmentioning
confidence: 99%